+0  
 
0
1
33
2
avatar+222 

Q1)

Q2)

 

thank you (:

Johnnyboy  Nov 9, 2018
 #1
avatar+2793 
+1

\(-1=\sqrt{3x-2}-\sqrt{4x+1}\\ \sqrt{4x+1}-1 = \sqrt{3x-2}\\ (4x+1)-2\sqrt{4x+1}+1 = 3x-2\\ 4x+2 - 2\sqrt{4x+1} = 3x-2\\ x+4=2\sqrt{4x+1}\\ x^2+8x+16 = 4(4x+1) = 16x+4\\ x^2 -8x + 12 = 0\\ (x-6)(x-2) = 0\\ x=6,~2\)

 

Let's check these solutions

 

\(\sqrt{18-2} - \sqrt{24+5} = 4 - 5 = -1\\ \sqrt{6-2}-\sqrt{8+1} = 2-3 = -1\)

 

Both solutions are valid.

Rom  Nov 9, 2018
 #2
avatar+2793 
+1

\(\dfrac{\dfrac{4}{2x-1}+\dfrac 1 4}{x+1}=\)

 

 

\(\dfrac{\dfrac{4\cdot 4 + 2x-1}{4(2x-1)}}{x+1} =\)

 

 

\(\dfrac{15+2x}{4(2x-1)(x+1)}\)

Rom  Nov 9, 2018

10 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.